Improving energy and economic performances of a typical sugarcane factory through energy indicator development, set-point optimization, and optimal sensor placement - Mkwananzi, Thobeka (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.